Genetically Engineered Virus Nanofibers as an Efficient Vaccine for Preventing Fungal Infection. Issue 7 (18th February 2016) - Huai, Yanyan; Dong, Shuai; Zhu, Ye; Li, Xin; Cao, Binrui; Gao, Xiang; Yang, Mingying; Wang, Li; Mao, Chuanbin
Abstract : Candida albicans (CA) is a kind of fungus that can cause high morbidity and mortality in immunocompromised patients. However, preventing CA infection in these patients is still a daunting challenge. Herein, inspired from the fact that immunization with secreted aspartyl proteinases 2 (Sap2) can prevent the infection, it is proposed to use filamentous phage, a human‐safe virus nanofiber specifically infecting bacteria (≈900 nm long and 7 nm wide), to display an epitope peptide of Sap2 (EPS, with a sequence of Val–Lys–Tyr–Thr–Ser) on its side wall and thus serve as a vaccine for preventing CA infection. The engineered virus nanofibers and recombinant Sap2 (rSap2) are then separately used to immunize mice. The humoral and cellular immune responses in the immunized mice are evaluated. Surprisingly, the virus nanofibers significantly induce mice to produce strong immune response as rSap2 and generate antibodies that can bind Sap2 and CA to inhibit the CA infection. Consequently, immunization with the virus nanofibers in mice dramatically increases the survival rate of CA‐infected mice. All these results, along with the fact that the virus nanofibers can be mass‐produced by infecting bacteria cost‐effectively, suggest that virus nanofibers displaying EPS can be a vaccine candidate against fungal infection. Abstract : A human‐safe nanofiber‐like virus, which surface‐displays a very short peptide such as an epitope by genetic means, is found to serve as an efficient vaccine for preventing fungal infection. Specifically, the virus nanofibers carrying a 5‐mer peptide motif in an infection‐associated antigen, once intraperitoneally injected into the mice, can induce the production of antibodies for the successful prevention.